Virus-Specific Secondary Plasma Cells Produce Elevated Levels of High-Avidity Antibodies but Are Functionally Short Lived - Krueger, Caroline C.; Thoms, Franziska; Keller, Elsbeth; Vogel, Monique; Bachmann, Martin F. (Frontiers in Immunology, 2019)
Most vaccines aim at inducing durable antibody responses and are designed to elicit strong B cell activation and plasma cell (PC) formation. Here we report characteristics of a recently described secondary PCs population that rapidly originates from memory B cells (MBCs) upon challenge with virus-like particles (VLPs). Upon secondary antigen challenge, all VLP-specific MBCs proliferated and terminally differentiated to secondary PCs or died, as they could not undergo multiple rounds of re-stimulation. Secondary PCs lived in bone marrow and secondary lymphoid organs and exhibited increased production of antibodies with much higher avidity compared to primary PCs, supplying a swift wave of high avidity antibodies early after antigen recall. Unexpectedly, however, secondary PCs were functionally short-lived and most of them could not be retrieved in lymphoid organs and ceased to produce antibodies. Nevertheless, secondary PCs are an early source of high avidity antibodies and induction of long-lived MBCs with the capacity to differentiate to secondary PCs may therefore be an underestimated possibility to induce durable protection by vaccination.